The Effect of Organic Chicken Manure Fertilizer on the Yield of Chicory Microgreens - Kusuma Wardani, Hana; iriani, Farida; Rahmawati, Aghnia (Ann Publisher, 2023)
Chicory is one of the interesting plants to cultivate microgreens. Microgreens cultivation began to trend carried out by urban communities in Indonesia during the pandemic, considering the Indonesian government's policy on the Implementation of Community Activity Restrictions. The application of organic fertilizers in microgreens cultivation planting media is important as a supplier of nutrients for the sustainability of plant growth and yield. Organic chicken manure fertilizer has been formulated consisting of chicken manure, kokopit, burnt husks and EM4 activator and fermented for 3 weeks, then tested against the growth and yield of chicory cultivated microgreens. How the effect of chicken manure organic fertilizer on the growth of chicory microgreens is the goal of this experiment. The experiment used a single-factor randomized group design consisting of five treatments and six groups. The treatment is the level of organic fertilizer dose of chicken manure, namely, 0, 125, 250, 375, and 500 g on an area of 27.10-2 M 2,100 plants with a total planting media weight of 2.103g per treatment. The experimental results showed that the level of chicken manure fertilizer 250 g per plot was the best for the variable response of fresh weight of plants, and fresh weight of roots, while the dose of 375 g had the best effect on germination, plant height, and root length.